Plan de mejora de los subsistemas de gestión del Talento Humano de selección, evaluación de desempeño y plan de capacitación en la empresa de seguridad VIGAR CIA. LTDA. - Alvarado Cando, Alejandra Marcela (2015)
This project aims to improve the subsystems Selection, Performance Evaluation and Training Plan in the area of Human Resources in the private security company VIGAR CIA LTDA., This improvement plan by a diagnostic performance of subsystems in question, showed that they are not performing systematic way while not carried out by a single area, so it was necessary to suggest improvements through tools that allow for order and harmony in the management of same. Over the years, human talent subsystems have been showing clear improvements in the way of recruiting, interviewing techniques, in making admission tests for companies, performance evaluation have created various formats and technological tools that yield qualitative and quantitative data, while these data allow us to be more specific training needs of staff. The improvement plan aims to propose changes in the way how to manage human talent and who should perform procedures to avoid excessive workload, improve the systematization of the subsystems, thus giving a proper progression of handling.